Recent Progress in Antimicrobial Nanomaterials - Díez-Pascual, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Based on a fundamental understanding of the interaction between bacteria and nanomaterials, this book highlights the latest research on the antimicrobial properties of nanomaterials and provides an invaluable blueprint for improving the antimicrobial performance of devices and products. This book introduces the reader to the progress being made in the field, followed by an outline of applications in different areas. Various methods and techniques of synthesis and characterization are detailed. The content provides insight into the ongoing research, current trends, and technical challenges in this rapidly progressing field. Therefore, this book is highly suitable for materials scientists, engineers, biologists, and technologists.